Appearance and Image: a Review of some Platonic Dialogues - Delgado, Carolina (Estudios de Filosofía, 2016)
The aim of the present paper is to determine the Platonic treatment of image. For this purpose, the most relevant sections of four dialogues Republic, Sophist, Cratyilus and Phaedo are analyzed. Textual examination has contributed to detect a distinction that operates in Platonic treatment, namely the difference between 'appearance' and 'image'. While the former is an ontologically loss-making illusion, the latter assumes the role of sensible instantiation of the ideal-intelligible realities. Based on this second kind, Plato has conceived the possibility of an ideal mimesis and a comeback to the knowledge of forms.